Photodynamic therapy for infected foot ulcers in people with diabetes mellitus: a systematic review - Brandão, Maria Girlane Sousa Albuquerque; Ximenes, Maria Aline Moreira; Sousa, Danilo Ferreira de; Vera, Vivian Saraiva; Barros, Lívia Moreira; Rabeh, Soraia Assad Nasbine; Costa, Idevania Geraldina; Araújo, Thiago Moura de (São Paulo Medical Journal, 2023)
BACKGROUND: Ulceration of the feet in patients with diabetes is a frequent complication that increases morbidity, mortality, hospitalization, treatment costs, and non-traumatic amputations. OBJECTIVE: To present a systematic review of the treatment of patients with diabetes mellitus and infected foot ulcers using photodynamic therapy. DESIGN AND SETTING: A systematic review was performed in the postgraduate program in nursing at the Universidade da Integração Internacional da Lusofonia Afro-Brasileira, Ceará, Brazil. METHODS: PubMed, CINAHL, Web of Science, EMBASE, Cochrane Library, Scopus, and LILACS databases were screened. The methodological quality, risk of bias, and quality of evidence of each study were assessed. Review Manager was used for the meta-analysis. RESULTS: Four studies were included. They highlighted significantly better outcomes in patient groups treated with photodynamic therapy than those in the control groups that were treated with topical col- lagenase and chloramphenicol (P = 0.036), absorbent (P < 0.001), or dry covers (P = 0.002). Significant improvements were noted in terms of the microbial load in the ulcers and tissue repair, with a reported reduction in the need for amputation by up to 35 times. Photodynamic therapy resulted in significantly better outcomes between the experimental and control groups (P = 0.04). CONCLUSION: Photodynamic therapy is significantly more effective in treating infected foot ulcers than standard therapies. SYSTEMATIC REVIEW REGISTRATION: International Prospective Register of Systematic Reviews (PROSPERO) - CRD42020214187, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=214187.